Can we predict high growth firms with the financial ratios? - Stjepan Srhoj (Financial Internet Quarterly, 2022)
This study attempts to predict high growth firm (HGF) status with financial ratios. Measures related to the firm's effectiveness in using assets to generate profits, EBITDA margin, debt ratio, equity-to-debt ratio and return on assets are associated with HGF status. While the financial ratios improve HGF prediction, prediction remains modest (AUC = 0.627). This study suggests it is difficult to assume a very good HGF forecast from only financial ratios; therefore, the recommendation for researchers and policymakers building models for predicting HGFs is to incorporate non-financial ratio variables, like the intangible innovation and team-related variables. Finally, study suggests a standardized reporting of prediction performance metrics in the out-of-sample and out-of-time simulation for HGF prediction studies.
Keywords: L1; M21; C53; G3; 330; high growth firms; prediction; financial ratios